Hypoprothrombinemia in the compensated form of hepatosplenic schistosomiasis: further studies - Nora Manoukian; Durval Rosa Borges (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
Coagulation abnormality is frequently observed in schistosomiasis patients but its pathophysiology has not been established. We measured, by immunodiffusion. the prothrombin-antigen concentration in 56 individuals; of these 19 with demonstrated compensated form of hepatosplenic schistosomiasis, 17 with cirrhosis and 20 were control subjects. Transaminases, albumin, transthyretin, prothrombin time, antithrombin III, factor VII, and fibrinogen were also evaluated. All parameters were altered in the cirrhotic group but only albumin, prothrombin and antithrombin III levels were altered in the schistosomiasis group. Ninety percent of the patients with cirrhosis and sixty percent of the patients with schistosomiasis had abnormal plasma levels of albumin, transthyretin, prothrombin-antigen, and/or antithrombin III; an impaired hepatic synthesis was responsible for these results. Conversely forty percent of the schistosomiasis patients with normal plasma concentrations of both albumin and transthyretin had decreased mean plasma levels of both prothrombin and antithrombin III. These results suggest that either proth rombin and antithrombin III are more sensitive markers of impaired hepatic synthesis in schistosomiasis than are levels of albumin and transthyretin combined, or a low grade chronic consumption of clotting proteins also occurs. Considering the latter hypothesis it is possible that the thrombin formed would be inhibited by antithrombin III with the complexed thrombin-antithrombin III being cleared by the liver. Consequently the plasma levels of both prothrombin and antithrombin would be decreased, but the level of fibrinogen would be preserved.